Internalisasi Nilai-Nilai Islam Melalui Program Jumat Barokah Dalam Membentuk Karakter Religius Peserta Didik SMK Negeri 3 Tuban - Muhammad Faliq Mubarrok Ilmi; Iis Aisaroh (Yayasan Al-Afif, 2025)
Student misconduct, including bullying and brawls, reflects a decline in religious character formation. This study describes the internalization of Islamic values through the